2019
DOI: 10.1039/c9an00160c
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase extraction method for stable isotope analysis of pesticides from large volume environmental water samples

Abstract: We validated a SPE-CSIA method that allows analysis of isotope ratios of mixtures of pesticides that commonly occur together in environmental water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 66 publications
4
61
0
Order By: Relevance
“…For one sample, accurate δ 37 C-ATR value was obtained even at a concentration below the instrumental LPIA of 0.05 nmol Cl on-column. The combination of this Cl-isotope method with large-volume SPE 28 will enable determination of chlorine isotope ratios of target herbicides in environmental water samples. Hydrolysis experiment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For one sample, accurate δ 37 C-ATR value was obtained even at a concentration below the instrumental LPIA of 0.05 nmol Cl on-column. The combination of this Cl-isotope method with large-volume SPE 28 will enable determination of chlorine isotope ratios of target herbicides in environmental water samples. Hydrolysis experiment.…”
Section: Resultsmentioning
confidence: 99%
“…These isotope ratios need to cover the measurement range to minimize distortion relative to the SMOC scale and to account for potentially variable calibration slopes for the same instrument over time. 11,26,27 Finally, it needs to be demonstrated that, in combination with large-volume solid-phase extraction (SPE) 28 , environmentally relevant concentrations can indeed be reached, which would open a route for analyzing the compounds at environmentally relevant levels with potentially large benefits for understanding the longterm fate of these compounds. As such model herbicides that bear one chlorine but numerous carbon atoms, challenging Cl-CSIA at environmental concentrations, we selected three of the most frequently detected contaminants in groundwater: atrazine (ATR), acetochlor (ACETO) and metolachlor (METO) ( Table S1, Supporting Information, SI).…”
mentioning
confidence: 99%
See 3 more Smart Citations